Social Learning Tools for Environmentally Sustainable Consumption Behavior in Primary Schools - Sharma, Meenakshi; Rani, Leela (European Journal of Sustainable Development, 2016)
UN’s Millennium Development Goals declared in 2010 stated sustainable consumption’s importance in ensuring environmental sustainability. Given the roles education, children and social learning process are expected to play in sustainability, this study aims to identify tools for active & passive social learning (SL) perceived by teachers (involved in delivering environmental education) as appropriate & effective for primary school children (chiefly focusing on environmentally sustainable consumption behaviorESCB). Study’s largely exploratory nature with a limited sample from Bhiwadi (India) was aimed at setting framework rather than generalization of results. Apart from interviewing fifty respondents from government and private schools with a semi-structured questionnaire (16 SL tools across 16 ESCBs), SL tools were also identified from text books. Data on was put through qualitative and quantitative analysis. Results showed that patterns in teachers’ preferences for SL tools were similar across school types but preferences only partly matched with recommendations from text books and/or research literature. Teachers’ qualitative statements for opportunities, constraints and opinions add to study’s strength. Findings hold useful implications for sustainability educators who aim to prod and inspire young minds for a sustainable environment. Insights would guide educationists to evolve effective SL tools for classroom experience.